Estudio comparativo de la alimentación en el rendimiento productivo de cerdos de engorde alimentados con balanceado de la línea exibal y balanceado comercial en la etapa inicial, crecimiento y engorde, en el cantón Chambo – Chimborazo. - Taipe Cando, Evelyng Mariana (2023)
Into research project, it was determined the productive performance in fattening pigs, they fed with commercial balanced and EXIBAL balanced in the initial, growth and fattening stage, further, it was elaborated a register, where was assessed the productive parameters. It was established comparisons between the research treatments; for determining the physicochemical characteristics. In the research, it was used two groups by 6 crossbred pigs, each one fed with commercial balanced (t1) and EXIBAL balanced (t2) from Landrace-Pietrain breed, the experimental phase lasted 90 days, the time established by EXIBAL balanced enterprise. Subsequently, it was made a statistical analysis with the Student's t test, in the weight gain variable, it was found, what the (t1) got a 48.13 kg value, while (t2) registered 41.98 kg, in the feed consumption, it was established, which statistically, there is no difference in the treatments, into feed conversion variable (t1), it has lower quantities in the initial stage and growth, while in (t2), it has a better result in the fattening stage. Making the physicochemical analyzes, it was checked, what the commercial feed has a 20.07% protein, 4.82% fat, 3.75% fiber, 5.6% ash and 10.74% moisture, on the other hand, the balanced EXIBAL contains 19.18% protein, 4.72% ash, 10.63% humidity, 5,04% fat and 3.83% fiber, finally, it was made a cost analysis, where the treatment one expenses were higher than the treatment two production costs.